1979
DOI: 10.1111/j.1365-2125.1979.tb04768.x
|View full text |Cite
|
Sign up to set email alerts
|

Labetalol in the treatment of patients with hypertension and renal function impairment.

Abstract: 1 Labetalol has been used to treat patients with renal hypertension or hypertension in the presence of renal functional impairment. In some patients changes in the glomerular filtration rate (GFR) were followed during the treatment. 2 Sixty patients were treated with labetalol for up to 24 months. Forty-nine of the patients were taking a diuretic and 23 were receiving additional antihypertensive therapy. The antihypertensive effect of labetalol has so far been assessed in 51 patients. Forty-six of these 51 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…At present, no information is available concerning the pharmacokinetics of labetalol in children, although there have been several reports of the successful clinical use of the drug in this age group (Bailey, 1979;Jones, 1979;Jureidini, 1980).…”
Section: Agementioning
confidence: 96%
See 1 more Smart Citation
“…At present, no information is available concerning the pharmacokinetics of labetalol in children, although there have been several reports of the successful clinical use of the drug in this age group (Bailey, 1979;Jones, 1979;Jureidini, 1980).…”
Section: Agementioning
confidence: 96%
“…Labetalol has been used successfully as an antihypertensive agent in patients with mild degrees of renal impairment without causing significant deterioration in renal function (Bailey, 1979;Thompson et al (1977). Wood et al (l982b) have studied the pharmacokinetics of intravenously administered labetalol in 4 patients with severe renal failure and creatinine clearance values in the region of 0.1 ml/sec (normal> 1.4 ml/sec).…”
Section: Chronic Renal Diseasementioning
confidence: 99%
“…Transient tiredness in three patients, and transient calf muscle pain in two patients were reported in a series of 17 patients by Andersson et al (1976). Urinary retention due to labetalol has been reported (Bailey, 1979;Dargie et al, 1976) and there have been isolated reports of patients suffering from vivid dreams that could have been due to labetalol (Hansson & Hiinel, 1976). Bolli et al (1976), in a series of 17 patients, reported two patients with mild constipation and one patient with angina, which worsened when labetalol was substituted for metoprolol.…”
Section: Side-effectsmentioning
confidence: 99%
“…Long term studies of renal function in hypertensive patients who had pre-existing compromised renal function have shown that labetalol treatment per se does not have any deliterious effect on the underlying renal function (Thompson et al, 1979;Bailey, 1979;Williams, 1979). It can be used alone or together with diuretics (Bailey, 1979), the dose of labetalol required to control BP being reduced due to the additive effect of the diuretic.…”
Section: Emergency Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation